Sustainable construction - Halliday, Sandy (New York, NY : Routledge, Taylor & Francis Taylor, 2019)
The second edition of Sustainable Construction provides a masterclass on the principles and techniques involved in the design and delivery of practical, affordable, high quality sustainable buildings and places. It presents precedents, theory, concepts and principles alongside 120 wide ranging case studies that highlight current best practice and encourage implementation. Topics in the book include:the history of ideas in sustainable construction; policy ; materials ; cost issues ; appraisal techniques ; environmental design ; energy ; water; construction processes; and urban ecology.(ed.).
1. Sustainability drivers 2. Policy and legislation 3. Cost Issues 4. Appraisal Tools & Techniques 5. Materials selection 6. Low-impact construction 7. Environmental Design: Heating, Cooling & Ventilation 8. Energy Generation 9. Lighting & Daylighting 10. Water & Sewage Management 11. Construction Processes 12. Urban Ecology
Includes bibliographical references and index.
Keywords: Sustainable construction; Sustainable buildings -- Design and construction